A multivariate analysis of growth and development parameters of the legume pad borer, Maruca testulalis, on variably resistant cowpea cultivars - Oghiakhe, S.; Odulaja, A. (Wiley, 1993)
Principal component analysis was employed to study the variation patterns in 18 cowpea cultivars developed for resistance to Maruca testulalis Geyer (Lepidoptera: Pyralidae) based on 7 developmental parameters of the pest on floral buds, flowers and sliced pods. On the whole, three developmental parameters: percentage pupation (V2), percentage emergence (V5) and growth index (V7) were the most important for the grouping of the cultivars with respect to M. testulalis damage. However, out of the three parameters, growth index (V7) had the highest factor score. Using the cluster analysis technique, the cultivars were sorted into five distinct groups for each part. The importance of these findings in the determination of protection periods for particular cultivars and cultural control studies of M. testulalis in cowpea are discussed.